Aqueous Synthesis of Ultrathin Platinum/Non‐Noble Metal Alloy Nanowires for Enhanced Hydrogen Evolution Activity. (31st July 2018) - Liu, Zhaojun; Qi, Jing; Liu, Moxuan; Zhang, Shumeng; Fan, Qikui; Liu, Hongpo; Liu, Kai; Zheng, Haoquan; Yin, Yadong; Gao, Chuanbo
Abstract: Although aqueous synthesis of nanocrystals is advantageous in terms of the cost, convenience, environmental friendliness, and surface cleanness of the product, nanocrystals of Pt and non‐noble metal alloys are difficult to obtain with controlled morphology and composition from this synthesis owing to a huge gap between the reduction potentials of respective metal salts. This huge gap could now be remedied by introducing a sulfite into the aqueous synthesis, which is believed to resemble an electroless plating mechanism, giving rise to a colloid of Pt‐M (M=Ni, Co, Fe) alloy nanowires with an ultrasmall thickness (ca. 2.6 nm) in a high yield. The sulfite also leads to the formation of surface M−S bonds and thus atomic‐level Pt/M–S(OH) interfaces for greatly boosted hydrogen evolution kinetics under alkaline conditions. An activity of 75.3 mA cm −2 has been achieved with 3 μg of Pt in 1 m KOH at an overpotential of 70 mV, which is superior to previously reported catalysts.